Functional Analyses of Patient-derived IgG Monoclonal Anticardiolipin Antibodies Using In Vivo Thrombosis and In Vivo Microcirculation Models - Pierangeli, Silvia S.; Liu, Xiaowei; Espinola, Ricardo; Olee, Tsawei; Zhu, Min; Harris, Nigel E.; Chen, Pojen P. (Thrombosis and Haemostasis, 2000)
Antiphospholipid antibodies (aPL) have been associated with thrombosis and pregnancy losses in patients diagnosed with antiphospholipid syndrome (APS) and enhance thrombus formation in vivo in mice, but the mechanism of thrombosis by aPL is not completely understood. It has been proposed that aPL may affect endothelial cell (EC) function and/or induce their activation, transforming their anticoagulant surface into procoagulant, thus predisposing to thrombosis. It has been proposed that aPL may affect EC cell function and/or induce their activation, transforming their anticoagulant surface into procoagulant, thus predisposing to thrombosis. This study proposes to test the hypotheses that some IgG anticardiolipins (IgG aCL) with thrombogenic properties in mice, exert their effects through activation of endothelium. We studied seven patient-derived monoclonal aCL for their thrombogenic properties in an in vivo pinch-induced thrombosis model, and their functional activities in activating EC by analyzing in vivo leukocyte adhesion to endothelium in microcirculation in venules in exposed murine cremaster muscle and in vitro adhesion molecule expression in cultured EC. The binding of the monoclonal aCL to EC was also tested. In addition to the previous identified thrombogenic IS2, four of the five new more IgG monoclonal aCL (from two patients) were found to be thrombogenic. Of these five thrombogenic aCL, three caused more in vivo leukocyte adhesion to EC in microcirculation, as compared to that induced by the H2 control human monoclonal IgG, and enhanced expression of adhesion molecules (particularly VCAM-1) on cultured EC. These data show that about 2/3 patientderived IgG monoclonal aCL are thrombogenic and suggest that some thrombogenic IgG aCL exert their effects through activating EC.Abbreviations: aCL, anticardiolipin antibodies; aPL, antiphospholipid antibodies; APS, antiphospholipid syndrome; CL, cardiolipin; dRVVT, dilute Russell’s viper venom time; EC, endothelial cells; ELISA, enzyme-linked immunosorbent assay; GP, glycoprotein; h, hour; HUVEC, human umbilicalvein endothelial cells; ICAM, intercellular adhesion molecule; KCT, kaolin clotting time; LA, lupus anticoagulant; PBS, phosphate-buffered saline; PL, phospholipid; sq, square; TBS, Tris-buffered saline; VCAM, vascular cell adhesion molecule; PMBC, peripheral mononuclear blood cells
Keywords: Antiphospholipid antibodies/syndrome; thrombosis; endothelial cell activation